2011
DOI: 10.1155/2011/940280
|View full text |Cite
|
Sign up to set email alerts
|

A Rearing Method forArgynnis (Speyeria) diana(Lepidoptera: Nymphalidae) That Avoids Larval Diapause

Abstract: We describe a rearing protocol that allowed us to raise the threatened butterfly, Argynnis diana (Nymphalidae), while bypassing the first instar overwintering diapause. We compared the survival of offspring reared under this protocol from field-collected A. diana females from North Carolina, Georgia, and Tennessee. Larvae were reared in the lab on three phylogenetically distinct species of Southern Appalachian violets (Viola sororia, V. pubescens, and V. pedata). We assessed larval survival in A. diana to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 6 publications
1
7
0
Order By: Relevance
“…The presence of particular Viola species did not appear to influence the activity of butterflies in our field sites. This result is consistent with laboratory rearing trials, which have not found any evidence of Viola preference in reproducing S. diana females, or developing larvae [11]. All of the violet species observed in this study are widely distributed in southeastern US forests [24].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The presence of particular Viola species did not appear to influence the activity of butterflies in our field sites. This result is consistent with laboratory rearing trials, which have not found any evidence of Viola preference in reproducing S. diana females, or developing larvae [11]. All of the violet species observed in this study are widely distributed in southeastern US forests [24].…”
Section: Discussionsupporting
confidence: 92%
“…While a number of violet species have been used to successfully rear S. diana in laboratory settings [8][9][10][11], to our knowledge there are no documented reports of Viola usage by S. diana from natural habitats. Evidence does suggest that S. diana may specialize in its nectar use, preferring high-quality nectar resources when available [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Each female Diana will lay thousands of eggs singly on ground litter in the vicinity of violets ( Viola spp., Violacea) in late summer before expiring (Allen, ; Ross & Henk, ; Wells et al ., ). First‐instar larvae hatch after several weeks and immediately burrow into the forest floor litter where they overwinter in diapause.…”
Section: Methodsmentioning
confidence: 97%
“…Nevertheless, some butterfly species appear to have greatly benefitted from population augmentation enabled by captive breeding programs [93]. Augmentation efforts are rare with Speyeria because they are difficult to successfully rear in captivity and the rearing process is labor intensive [94,95]. Captive reared S. zerene hippolyta have been used in a few conservation plans [96], but little other work has been done.…”
Section: Captive Rearingmentioning
confidence: 99%